A SISTEM PENDUKUNG KEPUTUSAN MEMILIH PERGURUAN TINGGI MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Anton Topadang; Yusni Nyura; M. Zainul Rohman (JSAI (Journal Scientific and Applied Informatics), 2025)
Choosing a university is a multi-criteria decision-making process that requires a systematic approach to ensure objective and transparent recommendations. This study applies the Analytical Hierarchy Process (AHP) to determine the priority weights of criteria in university selection. The research stages include constructing a decision hierarchy, conducting pairwise comparisons, calculating weights, and performing consistency validation. The results indicate that criterion K1 is the most dominant factor with a weight of 0.447, followed by K2 with 0.227 and K5 with 0.161. Meanwhile, K3 and K4 have relatively lower weights. The Consistency Ratio (CR) value of 0.038 confirms that the judgments are consistent and meet the acceptable threshold of CR < 0.1. These findings demonstrate that AHP provides a robust and measurable evaluation framework for university recommendation systems. The proposed model supports users in making informed decisions based on systematic and justifiable preference weighting.